The three failures of creationism : logic, rhetoric, and science - Fitch, Walter M., 1929-2011. (California : University of California Press, 2012)
Walter M. Fitch, a pioneer in the study of molecular evolution, has written this cogent overview of why creationism fails with respect to all the fundamentals of scientific inquiry. He explains the basics of logic and rhetoric at the heart of scientific thinking, shows what a logical syllogism is, and tells how one can detect that an argument is logically fallacious, and therefore invalid, or even duplicitous. Fitch takes his readers through the arguments used by creationists to question the science of evolution. He clearly delineates the fallacies in logic that characterize creationist thinki.
Cover; Title Page; Copyright Page; Table of Contents; Foreword; Chapter 1. Logic, Logical Fallacies, and Rhetoric; Chapter 2. The Basics; Chapter 3. Some Simple Math and Statistics; Chapter 4. "Young- Earth" Creationism; Epilogue: The Literal Meaning of Genesis; Acknowledgments; Glossary; Annotated Reference List; Index.
Print version record.
Keywords: Creationism; Religion and science; Logic; Evolution (Biology); Faith and reason; Creationism; Evolution (Biology); Faith and reason; Logic; Religion and science; RELIGION / Christian Theology / General; Electronic books